Determination of nitrofurans in animal feeds by liquid chromatography-UV photodiode array detection and liquid chromatography-ionspray tandem mass spectrometry - Barbosa, Jorge (2007)
Within the EU, the use of nitrofurans is prohibited in food production animals. For this reason detection of these compounds in feedingstuffs, at whatever limit, constitutes an offence under EU legislation. This detection generally involves the use of analytical methods with limits of quantification lowers than 1 mg kg-1. These procedures are unsuitable for the detection and confirmation of trace amounts of nitrofurans in feedingstuffs due to contamination. It is well known that very low concentrations of these compounds can be the source of residues of nitrofuran metabolites in meat and other edible products obtained from animals consuming the contaminated feed. The present multi-compound method was capable of measuring very low concentrations of nitrofurantoin (NFT), nitrofurazone (NFZ), furazolidone (FZD) and furaltadone (FTD) in animal feed using nifuroxazide (NXZ) as internal standard. Following ethyl acetate extraction at mild alkaline conditions and purification on NH2 column, the nitrofurans are determined using liquid chromatography with photodiode-array detection (LC-DAD). It was observed a CC[alpha] ranged from 50 to 100 [mu]g kg-1. The liquid chromatography-tandem mass spectrometric (LC-MS/MS) procedure was used to confirm the identity of the suspected presence of any of the nitrofuran compounds.